Initial Public Offerings as Lotteries: Skewness Preference and First-Day Returns - Green, T. Clifton; Hwang, Byoung-Hyoun (Management Science, 2012)
We find that initial public offerings (IPOs) with high expected skewness experience significantly greater first-day returns. The skewness effect is stronger during periods of high investor sentiment and is related to differences in skewness across industries as well as to time-series variation in the level of skewness in the market. IPOs with high expected skewness earn more negative abnormal returns in the following one to five years. High expected skewness is also associated with a higher fraction of small-sized trades on the first day of trading, which is consistent with a greater shift in holdings from institutions to individuals. The results suggest that first-day IPO returns are related to a preference for skewness. This paper was accepted by Brad Barber, Teck Ho, and Terrance Odean, special issue editors.